Growth performance, carcass traits, and meat quality of Wagyu crossbred with Kamphaengsaen, Brahman, and Thai Holstein Friesian cattle - Prayad Thirawong; Lukman Abiola Oluodo; Patipan Hnokaew; Sirirat Buaphan; Saowaluck Yammuen-Art (Veterinary Integrative Sciences)
This study compared the growth performance, carcass characteristics, and meat quality of steers; Wagyu × Kamphaengsaen (WKPS), Wagyu × Brahman (WBR), and Wagyu × Thai Holstein Friesian (WTHF). Twenty-one crossbred Wagyu with a mean body weight of 395.10±43.89 kg were randomly assigned to three groups (n=7). All steers were fed the same diet from 19 months until slaughter age at 26 months. Growth performance indices were divided into two periods, at 19 – 22 and 23 – 26 months. The WTHF was found to have better body weight gain, average daily gain, and feed conversion ratio compared to WBR and WKPS (p<0.05). The longissimus dorsi muscle was used to compare the meat quality traits. Thai Holstein Friesian crossbred cattle were found to have higher growth performance (p<0.05) and carcass characteristics (p<0.05); WKPS had a higher meat color value for a*, while L* and b* meat color values were higher with the WBR group (p<0.05); and WTHF meat had higher fat composition and lower shear force (p<0.05). The results show that WTHF cattle had better growth performance and provided higher fat content for high meat quality attributes, WBR had higher meat color values, while the WTHF cattle provided better meat quality attributes among the group